Molecular Docking of Curcumin With Breast Cancer Cell Line Proteins - Asita Elengoe; Nishalani Devi Sundramoorthy (Mazandaran University of Medical Sciences, 2020)
Background: Breast cancer is known as the most widely recognized dangerous tumors; therefore, the most common reason for mortality among all instances of harmful neoplastic illness in females. This is because the lack of specific signs and symptoms at the early stage and at the aggressive nature. Currently, breast cancer treatment such as chemotherapy, surgery and radiotherapy has not been effective. Objectives: In this study, three-dimensional (3D) structures of caspase 3, mucosal addressin cell adhesion molecule 1 (MADCAM1) and nuclear factor NF-kappa-B-p105 subunit (breast cancer cell line proteins) were created; and their binding interaction between proteins and curcumin through molecular docking approach were studied. Methods: The proteins were created using Swiss model and viewed by PyMol software. The physical and chemical characters of the proteins were analysed by Expasy's ProtParam Proteomics server. Besides that, the secondary structures of the proteins were analysed by SOPMA (Self Optimized Prediction Method from Alignment) server. After that, they were evaluated by PROCHECK, ProQ, ERRAT, and Verify3D analysis. Lastly, the breast cancer cell line proteins were docked with curcumin using BSP-Slim server. Results: All the protein structures were good quality and within the acceptable range. The curcumin showed the binding energy with caspase 3, mucosal addressin cell adhesion molecule 1 and nuclear factor NF-kappa-B-p105 subunit at 4.140, 7.201 and 3.165 kcal/mol respectively.  Conclusion: The nuclear factor NF-kappa-B-p105 subunit had the strongest bond with curcumin. Curcumin can be potential drug for breast cancer treatment. Therefore, it can further be investigated in laboratory experiments.